The role of vitamin D in increasing circulating T regulatory cell numbers and modulating T regulatory cell phenotypes in patients with inflammatory disease or in healthy volunteers: A systematic review. - Sheila A Fisher; Mana Rahimzadeh; Charlotte Brierley; Betty Gration; Carolyn Doree; Catherine E Kimber; Alicia Plaza Cajide; Abigail A Lamikanra; David J Roberts (PLoS ONE, 2019)
BACKGROUND:The evidence for vitamin D and other agents that experimentally modulate T regulatory cells (Tregs) for the treatment of patients with autoimmune or allergic diseases has not been established. OBJECTIVE:We have undertaken a systematic review of randomised controlled trials to assess the efficacy of vitamin D, vitamin A, niacin and short-chain fatty acids in enhancing absolute Treg numbers and phenotypes in patients with inflammatory or autoimmune disease. METHODS:This systematic review was conducted using a predefined protocol (PROSPERO International prospective register of systematic reviews, ID = CRD42016048648/ CRD42016048646). Randomised controlled trials of patients with inflammatory or autoimmune disease or healthy participants which compared either oral vitamin D or vitamin A or short-chain fatty acids with control or placebo and measured the absolute concentration of proportion of Tregs were eligible for inclusion. Searches of electronic databases (CENTRAL, MEDLINE, EMBASE, CINAHL, PUBMED and Web of Science) identified eight eligible independent trials (seven autoimmune disease trials, one trial of healthy subjects). Data were extracted by two reviewers and the risk of study bias was assessed using Cochrane Collaboration methodology. RESULTS:Planned meta-analysis was not possible due to the heterogeneous nature of the studies. Nevertheless, in five trials of autoimmune disorders which measured the proportion of Tregs, a higher proportion was observed in the vitamin D group compared to controls at 12 months in all but one trial. In the trial of healthy subjects, a significant difference was reported, with a higher percentage of Tregs observed in the vitamin D group (at 12 weeks, mean 6.4% (SD 0.8%) (vitamin D) vs 5.5% (1.0%) (placebo). There were no trials to assess the efficacy of vitamin A, niacin and short-chain fatty acids in enhancing absolute Treg numbers. CONCLUSIONS:Vitamin D supplementation may increase Treg/CD3 ratios in both healthy individuals and patients with autoimmune disorders and may increase Treg function. There remains a need for further suitably powered clinical studies aimed at enhancing Treg numbers and/or function.